STRATEGI PENGEMBANGAN POTENSI WISATA AIR TERJUN FIJI DI DESA LEMUKIH, KECAMATAN SAWAN, KABUPATEN BULELENG - Kadek Resta Dewi; Putu Agus Prayogi; Ida Bagus Nyoman Krisna Prawira Yuda (Jurnal Cakrawala Ilmiah, 2026)
Background: Fiji Waterfall in Lemukih Village, Sawan District, Buleleng Regency possesses significant ecotourism potential due to its unique triple-waterfall formation, pristine tropical landscape, and cultural-spiritual values. Despite these advantages, the destination remains underdeveloped because of limited tourism facilities, inadequate institutional capacity, and insufficient promotion. This study aimed to identify the tourism potential, examine the constraints affecting its development, and formulate appropriate strategies to enhance the competitiveness and sustainability of Fiji Waterfall as a community-based ecotourism destination. Methods: This study employed a qualitative descriptive approach using a case study design. Data were collected through participatory observation, in-depth interviews with key stakeholders, including the village head, community leaders, local tourism managers, tourists, and an academic expert, as well as document analysis. The tourism potential was analyzed using the 4A framework (Attraction, Accessibility, Amenities, and Ancillary), while strategic development priorities were formulated using SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. Data were analyzed following the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, with source triangulation used to ensure data credibility. Results: The findings indicate that Fiji Waterfall possesses outstanding tourism attractions, including a rare triple-waterfall landscape, scenic trekking routes, and spiritual tourism resources. However, its development is constrained by inadequate infrastructure, limited tourism facilities, insufficient human resource capacity, weak institutional governance, and limited financial support. SWOT analysis suggests that the most appropriate development strategies emphasize improving internal capacities (W–O strategy) through institutional strengthening, infrastructure enhancement, human resource development, and digital marketing, while simultaneously implementing destination protection strategies (S–T strategy) through environmental conservation, visitor management, and community participation. Conclusion: Fiji Waterfall has considerable potential to become a sustainable community-based ecotourism destination. Strengthening local institutions, improving tourism infrastructure, enhancing human resource competencies, and fostering Pentahelix collaboration among government, local communities, academia, businesses, and the media are essential for achieving sustainable tourism development while preserving the area's environmental and cultural values.